The Impact of Losses in Cable Selection for Distribution Circuit in Malaysia - Low, Siew Yi; Gan, Chin Kim (2013)
This paper describes the impact of losses in cable selection for distribution circuit in Malaysia. A minimum life cycle cost methodology is utilized as a basic for circuit design. Minimum life-cycle cost methodology is a method that balances the capital cost against the cost of circuit losses. The result obtained shows the optimal utilisation of 11kV distribution cable in Malaysia is quite low, in the range of 32% to 41%. Parametric analyses on discount rate, load factor and electricity price were carried out to validate the robustness of the results.